Nutrition and maternal health: a mapping of Australian dietetic services - Shelley Ann Wilkinson; Elin Donaldson; Jane Willcox (BMC, 2020)
Abstract Background Strong associations between diet and maternal and child outcomes emphasise the importance of evidence-based care for women across preconception, antenatal and postnatal periods. A 2008 survey of Australian maternal health dietetic services documented critically low resourcing with considerable variation in staffing levels and models of care. This study repeated the survey to examine resourcing in Australian maternal health services. Methods A cross-sectional online survey was emailed to publicly-funded Australian maternal health dietetic services in May 2018. Quantitative and qualitative variables collected across preconception to postnatal services (including diabetes) included; births per year (BPY), number of beds, staffing (full time equivalents; FTE), referral processes, and models of care. Results were collated in > 5000; 3500 and 5000; and < 3500 BPY. Results Forty-three eligible surveys were received from seven states/territories. Dietetic staffing levels ranged from 0 to 4.0 FTE (> 5000 BPY), 0-2.8 FTE (3500-5000 BPY), and 0-2.0 FTE (< 3500 BPY). The offering of preconception, antenatal and postnatal services varied significantly between hospitals (format, staffing, referral processes, delivery models). Few sites reported service effectiveness monitoring and only one delivered gestational diabetes mellitus care according to nutrition practice guidelines. Low staffing levels and extensive service gaps, including lack of processes to deliver and evaluate services, were evident with major concerns expressed about the lack of capacity to provide evidence-based care. Conclusions Ten years after the initial survey and recommendations there remains an identified role for dietitians to advocate for better staffing and for development, implementation, and evaluation of service models to influence maternal nutrition.